DISSIMILAR METALS CONNECTION THROUGH FRICTION STIR WELDING (CU-AL) - Evgeny Sergeyevich Bubenok (Advanced Engineering Research)
The aim of the paper is to analyze the existing techniques of producing copper and aluminum compounds. The subject matter was to study the possibility of using FSW for producing copper and aluminum compounds. The process of producing the copper and aluminum lap joints is described, welding conditions are discussed. The copper and aluminum overlap joints microstructure is investigated. The factors affecting the strength of copper and aluminum lap joints implemented through FSW are analyzed. The corrugation effect is investigated, and the remaining hole is studied to the strength of the welded joint. Stress distribution diagrams in the copper and aluminum lap joints are shown. The tests to the strength of various lap joints are resulted, the weld cut structure is analyzed, its processibility is estimated, and the joint strength improvement method is presented.